Strong solutions to the Navier–Stokes–Fourier system with slip–inflow boundary conditions. Issue 12 (29th July 2013) - Piasecki, T.; Pokorný, M.
Abstract: We consider a system of partial differential equations describing the steady flow of a compressible heat conducting Newtonian fluid in a three‐dimensional channel with inflow and outflow part. We show the existence of a strong solution provided the data are close to a constant, but nontrivial flow with sufficiently large dissipation in the energy equation. Abstract : The authors consider a system of partial differential equations describing the steady flow of a compressible heat conducting Newtonian fluid in a three‐dimensional channel with inflow and outflow part. They show the existence of a strong solution provided the data are close to a constant, but nontrivial flow with sufficiently large dissipation in the energy equation.